Optimal forest taxation under private and social amenity valuation - Erkki Koskela; Markku Ollikainen (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper analyzes the socially optimal forest taxation in the rotation framework when the government has a binding tax revenue requirement. In the Faustmann model the optimal design of taxation consists of non-distortionary taxes, such as site productivity tax, site value tax or profit tax. A combination of distortionary unit (or yield) tax and timber tax can also be used to collect the tax revenue in a nondistortionary way. In the Hartman model with forest amenity services as a public good, the optimal design consists of a non-distortionary tax and a Pigouvian tax, which adjusts the private rotation age to the socially optimal one. Now only the site productivity tax is non-distortionary, while unit, yield, timber, site value and profit taxes generally serve as corrective Pigouvian taxes. Finally, in the absence of a non-distortionary tax, if the marginal valuation of amenity services is non-decreasing with the age of forest stand, a combination of unit (or yield) and timber taxes can be used to both tax revenue collection and Pigouvian correction.
Keywords: Q23; H21; 330; rotation age; forest amenities; optimal forest taxation; Forststeuer; Optimale Besteuerung; Internalisierung externer Effekte; Forstökonomie; Soziale Wohlfahrtsfunktion; Wohlfahrtseffekt; Theorie